Implementasi Manajemen Sistem Pendidikan pada Tingkat Dasar dan Menengah: Tantangan dan Solusi - Sarwoedi; Adekamisti, Revi; Handayani, Tri; Novianty, Elva; Harmi, Hendra; Sutarto; Fakhruddin (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
This study explores the challenges in implementing education management systems at primary and secondary levels in Indonesia, particularly concerning quality disparities between urban and rural areas. The purpose of this research is to identify challenges in the implementation of education management, including aspects of teacher distribution, technology access, and curriculum flexibility, and to offer relevant solutions. The main issues include uneven teacher distribution, limited technology access in remote areas, and a rigid curriculum that is insufficiently responsive to local needs. This study uses a literature review method by analyzing various secondary sources, such as academic journals, government reports, and related publications, to gain a comprehensive understanding. The findings reveal that major challenges in education management include limited educational infrastructure in remote areas, uneven teacher distribution, and restricted access to professional training for teachers. The suggested solutions include evidence-based policy implementation, improved access to educational technology, and curriculum adjustments tailored to local contexts. This study emphasizes the importance of an adaptive, evidence-based management approach to address educational quality disparities across different regions in Indonesia.